Orchid Agribusiness Development Strategy in Magelang Regency - Sumastuti, Efriyani (EconBank: Journal of Economics and Banking, 2024)
The growth of the floriculture industry, particularly orchid production, in Indonesia has been in the spotlight in recent decades. Magelang Regency, as one of the significant orchid production centers, faces challenges in optimizing its orchid agribusiness potential, especially in Sidomulyo Village. Despite experiencing rapid growth, there are still obstacles such as access to capital, business management, marketing, and production sustainability. The Rural Agribusiness Business Development Program (PUAP) launched since 2012 has also not provided optimal results. This study aims to identify new strategies in developing orchid agribusiness in Magelang Regency, focusing on the application of eco-friendly agribusiness innovations and smart integrated farming systems. Through a hierarchical analysis approach (AHP) and primary data obtained from informants in Sidomulyo Village, this study prioritizes key factors in the development of orchid agribusiness, including capital, human resources, institutions, infrastructure, and marketing promotion. The results showed that the development of infrastructure facilities is a top priority in the development of sustainable PUAP in Magelang Regency, followed by promotion and marketing. The implementation of the smart integrated farming system model, especially in terms of providing sustainable cultivation inputs, is emerging as a key strategy to improve the efficiency and sustainability of orchid production. In conclusion, this study offers a new perspective in overcoming the challenges of orchid agribusiness development in Magelang Regency, emphasizing the importance of innovation and sustainability in every aspect of the business. It is expected that this research can make a significant contribution to the development of orchid agribusiness and inclusive and sustainable village development in the region.